Correlation to predict heat transfer characteristics of a closed-end oscillating heat pipe at normal operating condition - Rittidech S. (2014)
This paper describes the effect of dimensionless parameters on the characteristics of heat transfer in a closed-end oscillating heat pipe (CEOHP). The parameters studied in this paper are; (i) Bond numbers, (ii) Froude numbers, (iii) Weber numbers, (iv) Prandtl numbers and (v) Kutateladze numbers. Experiments were conducted to find out their effects on the heat transfer rates of copper CEOHPs with inner diameters of 0.66, 1.06 and 2.03 mm. The lengths of the evaporator, adiabatic and condenser sections were equal and changed to 15, 10 and 5 cm. The total lengths of the CEOHPs were 15, 10 and 5 m. R123, ethanol and water were used as the working fluids with a filling ratio of 50%. The evaporator was heated by hot water, while the condenser section was cooled by a solution of water and ethylene glycol with a 1:1 mixing ratio by volume. The angle of the CEOHPs used in the experiments was set at 0° (horizontal mode) with a controlled vapor temperature of 50 °C. When the system reached the steady state, the temperature and the flow rate of the cooling substance was recorded in order to calculate the heat transfer rate of the CEOHP. It was found from the experiment that when R123 was used, the inner diameter affected the heat flux. The results of the experiment showed that when the inner diameter was larger, so was the heat flux. The result for ethanol showed the opposite; when the inner diameter increased, the heat flux decreased. Because of insufficient data obtain from using water as working fluid, the heat flux could not be reliably measured. The evaporator section lengths also affected the heat flux. The evaporator length of 15 cm gave the lowest value of heat flux. When the number of turns decreased, the heat flux increased and when n is equal to 14, heat flux is still increasing with an decrease in n. The results of the experiment also showed that the correlation equation could be used to predict the heat flux and that the operation map could predict the operational range and the inner diameter. © 2002 Elsevier Science Ltd. All rights reserved.